Parallel Implementations of Cellular Automata-Based Traffic Models Using the AGILA Cluster Computer - Provido, Eden Delight B. (Philippine computing journal)
Previous studies have shown that the simulation using cellular automata models traffic based on theoretical assumptions and data from the classical theory of traffic dynamics. In this study, the parallel implementation of the one-lane and two-lane freeway models of vehicular traffic dynamics on the AGILA cluster computer are presented. The implementation technique used is the Master-Slave techique. Results gathered using the parallel implementations show that the present model benefits from parallelization.